Organic, inorganic and total bromine in the extratropical tropopause and lowermost stratosphere in fall 2017: Origins, transport pathways and consequences for ozone - Rotermund, Meike Kerrin (2021)
Inferred total bromine (Brtot) was measured in the upper troposphere (UT) and lower stratosphere (LS) from a research aircraft over the North Atlantic and north western Europe in fall 2017 during the WISE (Wave-driven ISentropic Exchange) campaign. The LS weighted-mean Brtot is 19.2 +/- 1.2 ppt. A closer look into organic and inorganic bromine, as well as simultaneously measured transport and air mass lag-time tracers, suggests that bromine-rich air masses persistently protruded into the LS in fall creating a high bromine region (HBrR). A subsection, HBrR*, has a Brtot weighted average of 20.9 +/- 0.8 ppt. The most probable source region is former tropical UT air with a Brtot weighted mean of 21.6 +/- 0.7 ppt. A secondary smaller source is transport across the extratropical tropopause. Lagrangian transport modelling quantifies these multi-pathway contributions to the LS and HBrR. Further, the influences of the Asian monsoon and its tropical adjacent regions as well as tropical cyclones from Central America on bromine are discussed. And lastly, the consequences of ~1-2 ppt additional bromine in the tropical UT are simulated by a global chemistry transport model resulting in 3.1 +/- 0.7% ozone decrease within the 20 K potential temperature layer directly above the tropopause.